2006
DOI: 10.1103/physrevlett.96.096105
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-Independent Kinetics in the Vapor-Liquid-Solid Growth of Si Nanowires

Abstract: We examine individual Si nanowires grown by the vapor-liquid-solid mechanism, using real-time in situ ultra high vacuum transmission electron microscopy. By directly observing Au-catalyzed growth of Si wires from disilane, we show that the growth rate is independent of wire diameter, contrary to the expected behavior. Our measurements show that the unique rate-limiting step here is the irreversible, kinetically limited, dissociative adsorption of disilane directly on the catalyst surface. We also identify a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
245
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(277 citation statements)
references
References 35 publications
30
245
1
1
Order By: Relevance
“…A good example of this behaviour is seen in the structures of semiconductor nanowires, often grown by the vapor-liquid-solid (VLS) method. 12,13) InP is cubic (zinc blende) in the bulk but found to take the hexagonal Wurtzite structure in nanowires. 14,15) Other III-V semiconductors, such as GaP and GaAs, are apparently not as close to being unstable as nanowires in the cubic phase; nevertheless, they show a strong trend towards hexagonal stacking along their cubic 111 crystal directions by the introduction of frequent stacking faults.…”
Section: Phase Diagramsmentioning
confidence: 99%
“…A good example of this behaviour is seen in the structures of semiconductor nanowires, often grown by the vapor-liquid-solid (VLS) method. 12,13) InP is cubic (zinc blende) in the bulk but found to take the hexagonal Wurtzite structure in nanowires. 14,15) Other III-V semiconductors, such as GaP and GaAs, are apparently not as close to being unstable as nanowires in the cubic phase; nevertheless, they show a strong trend towards hexagonal stacking along their cubic 111 crystal directions by the introduction of frequent stacking faults.…”
Section: Phase Diagramsmentioning
confidence: 99%
“…A broad range of semiconductor nanowires, including Si, Ge [13,14], III-Vs [15,16] and II-VIs [17][18][19][20][21], have been grown using chemical vapor deposition (CVD), thermal evaporation, solvothermal synthesis and molecular-beam exitaxy (MBE) based on the metal-catalyzed vaporliquid-solid (VLS) mechanism [22]. However, only a few reports on the synthesis of tellurium-based NWs have been published so far.…”
mentioning
confidence: 99%
“…However, in recent years, both experimentalists and theorists [4][5][6][7] have demonstrated that thin semiconductor nanowires with diameter smaller than 50 nm can grow and show interesting growth behaviors. For example, in the growth of thin Si and ZnSe nanowires catalyzed by Au particles, smaller nanowires have higher growth rates compared to thicker ones, [5][6][7] and most of ultrathin nanowires grow at relatively low temperatures. Recently, Kodambaka et al 8 demonstrated by in-situ transmission electron microscopy (TEM) that solid catalysts led to Ge nanowire growth even at a temperature below the eutectic point.…”
mentioning
confidence: 99%